Avaliação de vacina recombinante de ortologo de subolesin em cães contra o carrapato Rhipicephalus snguineus (Latreille, 1806) - Tsuruta, Suzana Akemi (2008)
The R. sanguineus is the tick with most world wide distribution and represents, as curiosity, the unique genus in Brazil. This acarus is associated to the presence of its host, the dog, and is used as a vector to agents of high importance diseases such as canine erliquiosis and babesiosis and humans botonose and spotted fever. The present paper had the aim to evaluate the efficiency and to characterize the induced immune answer by a mosquito subolesin recombinant vaccine and orhtolog of the tick Ixodes scapularis against R. sanguineus. In this evaluation six dogs were vaccine inoculated and other six were inoculated only with the adjuvant. The animals were then challenged with experimental infestation to evaluate vaccine s efficiency. The tick dog s cutaneous reaction was rated by histopathology. Hyper sensibility cutaneous test with tick antigens was done to estimate vaccinated dog s immune answer alterations. Antibodies titles against the vaccinal antigen were estimated by ELISA. Although there was a decrease in the recovering rate of grubs and nymphs in the vaccinated animals there wasn t statistical differences in biological parameters between the two experimental groups. The vaccinated animals presented more discreet hemorrhages, necrosis and edema at the tick s fixation point. The cutaneous hyper sensibility of vaccinated animals was exacerbated. The vaccinated animals presented an elevation in anti-subolesin antibodies. It s been concluded that the tested vaccine doesn t induce to a remarkable resistance to the tick R. sanguineus in spite of it can modifcate the hot s reaction.